Sosialisasi dan Pelatihan Bagi Aparat Kampung Dalam Pengelolaan Arsip Digital Menuju Kampung Tertib Administrasi di Kampung Kweel Kabupaten Merauke - Agung, Rachmat; Majid, Ilham (Universitas Pahlawan Tuanku Tambusai, 2025)
Organizing village government administration digitally is a necessity. This is due to the increasingly widespread need for the availability of accurate and fast village development information. The aim to be achieved in this service activity is to carry out training for Kweel Village Officials in the context of utilizing digital archives for structuring village government administration. The method used is the transfer of knowledge through training and assistance in using Google Drive as a medium for archive management and information presentation for village government officials. The results of this activity are increasing knowledge and skills, as evidenced by changes in behavior on a scale of 76-100, namely the high category. This is also proven by the increase in participants' conceptual understanding and practice in managing documents digitally in Kweel Village, an average increase of 25%. It is hoped that the results of this activity can provide solutions to archival problems in Kweel Village, Merauke Regency to move towards an orderly administrative village.